TINGKAT PENGETAHUAN ORANG TUA TENTANG STIMULASI PERKEMBANGAN ANAK PRA SEKOLAH USIA 3-5 TAHUN - Dianita Primihastuti (Akademi Kebidanan Griya Husada Surabaya, 2020)
Introduction: The role of parents in children aged 3-5 years is very important. Father and mother as the nearest person is a child's first teachers in life to know. Unfortunately, many parents both father and mother who had spent a year in order to meet the necessities of life. This condition makes the parent unable to provide an optimal stimulus for the development of the child. This study aims to describe the level of parental knowledge about stimulation of the development of pre-school children aged 3-5 years in the village of RT 01 RW 01 Pekayon Kranggan village, Mojokerto. Method: In this study using a descriptive research design, the population is parents of children aged 3-5 years in RT 01 Village Kranggan Mojokerto. Sample of 24 people, sampling is purposive sampling. The variables studied were parental knowledge about stimulation of the development of pre-school children aged 3-5 years, the method of data collection was a questionnaire. Result: The survey results revealed that 24 respondents surveyed earned 4 respondents (16.7%) can provide good stimulation to their children, 9 respondents (37.5%) parents provide enough stimulation, and 11 respondents (45.8%) parents provide less stimulation to their children. Discussion: From the results of these data found that the picture of the level of parental knowledge (45,8%) about child development stimulation because parents do not know the benefits of providing stimulation to their children.